1995
DOI: 10.1002/bscb.19951040409
|View full text |Cite
|
Sign up to set email alerts
|

PREPARATION OF UNIFORMLY DISPERSED MoP/AL2o3 CATALYSTS

Abstract: Several preparative factors which determine the properties of MoP/Al203 catalyst have been studied. With sequential impregnation, the Mo dispersion is always worse than with co-impregnation, while in co-impregnation the pH of the impregnating solution should be properly adjusted according to the P content. Since both mdybdate and phosphate Ions interact strongly with the alumina surface, they can adsorb directly at the pore mouths and inhibit other ions to enter the pores. Especially in the case of sequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This dopant is widely used in industrial formulations since there is general agreement that it leads to an increase in HDS activity [36–42] by reducing the interactions between the active phase and the support as phosphates block the basic surface Al‐OH sites that selectively interact with the Mo active phase. It has also been reported that phosphorus can improve Mo dispersion [43] . Nonetheless, this beneficial effect is highly dependent on the P‐loading and on the incorporation method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dopant is widely used in industrial formulations since there is general agreement that it leads to an increase in HDS activity [36–42] by reducing the interactions between the active phase and the support as phosphates block the basic surface Al‐OH sites that selectively interact with the Mo active phase. It has also been reported that phosphorus can improve Mo dispersion [43] . Nonetheless, this beneficial effect is highly dependent on the P‐loading and on the incorporation method.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reportedt hat phosphorusc an improveM od ispersion. [43] Nonetheless, this beneficial effect is highly dependento nt he P-loadinga nd on the incorporation method. For instance, co-impregnation of phosphorusa nd metal precursors modifies the chemical structure of the depositedp recursor by forming heteropolyanions, [19,38,40] which may have an effect both on Mo dispersion and posterior catalysta ctivation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported *Present address : Escuela de lngenieria Quimica, UMSNH, Mordia, Mich., Mexico that phosphorus not only enhances the solubility of molybdate by the formation of phosphomolybdate complexes and thus makes catalyst preparation easier (see references in ref. 7), but also that it increases the HDN activity of NiMolAlnOs catalysts (8-1 0). However, the beneficial catalytic effects of phosphorus were observed In studies of quinoline HDN, where not only C-N bond breaking, but also hydrogenation of benzene and pyridine rings are Involved in the reaction network and are needed prior to C-N bond breaking.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, Eijsbouts et al [8] reported an increase in quinoline conversion to hydrocarbons and an increased selectivity for unsaturated nitrogen-free hydrocarbons with the addition of P in the NiMo/γ-Al 2 O 3 catalyst. Jian et al [9] also reported the boost effect of P on the HDN of ortho-propylaniline (OPA) and reached a decision that P caused the advantage adsorption of OPA on the catalyst because of the production of increased number of catalytic sites.…”
Section: Introductionmentioning
confidence: 99%